Pop-up governance: Transforming the management of migrant populations through humanitarian and security practices in Lesbos, Greece, 2015–2017. (December 2020) - Papada, Evie; Papoutsi, Anna; Painter, Joe; Vradis, Antonis
This paper intervenes in recent debates on humanitarianism and security in migration by introducing the notion of 'pop-up governance'. It reflects on our two year-long fieldwork on Lesbos, Greece at the peak of Europe's migrant reception crisis (2015–2017). We present recent developments in border and migration management in the EU and we position these within recent migration debates. We then present the two main facets guiding migrant reception and governance in Lesbos, namely humanitarianism and security. Through our interviews with humanitarian and security actors we show how top-level government decisions followed and resembled the flexibility and adaptability of humanitarian and security operations. We define this turn as 'pop-up governance', which comprises a practice-based, abruptly introduced and retractable set of governance mechanisms responding to the situation at hand. We argue that the seemingly disorganised management of migration actually bore hallmarks of a new, flexible and adaptable mode of governance. Finally, we show how 'pop-up governance' can help move beyond present understanding of governance based either on the rule or its exception. This has important implications for our comprehension of migration, humanitarianism, security and the governance of vulnerable populations and contemporary socio-political crises.